PENGEMBANGAN SISTEM INFORMASI PERPUSTAKAAN MENGGUNAKAN JAVA NETBEANS IDE (Studi Kasus : SMK NU Wado Kedungtuban) - Umi Rosidah; Adhika Pramita Widyassari (SIMETRIS, 2018)
Service and management of SMK NU Wado Kedungtuban library data still uses the manual method by recording member data, borrowing, repaying and reporting still using books as a medium for recording loan transactions so that it is less effective and efficient. The purpose of research is the design, development and implementation of library information systems to help the process of library service management and data implementation using Java NetBeans IDE-based information systems. The design of the information system is modeled into diagrams in UML (Unified Modeling Language) and the method of developing the System Development Life Cycle (SDLC) with the Waterfall model. This Mobile Based Library Information System Research is expected to help library staff in the process of managing library data, as well as assist students in the process of finding books so that it is easier.